Direct Chirality Recognition of Single‐Crystalline and Single‐Walled Transition Metal Oxide Nanotubes on Carbon Nanotube Templates. Issue 44 (14th September 2018) - Shen, Boyuan; Xie, Huanhuan; Gu, Lin; Chen, Xiao; Bai, Yunxiang; Zhu, Zhenxing; Wei, Fei
Abstract: Chirality is a significant structural feature for chemistry, biology, physics, and materials science, and especially determines the electrical, mechanical, and optical properties of diverse tubular structures, such as carbon nanotubes (CNTs). To recognize the chirality of nanotubes, templates are introduced as potential tools to obtain crystalline samples with visible chiral fringes under electron microscopes. However, few efforts show optimistic results, and new understanding is desired to control the sample quality with CNT templates. Here, a synthesis strategy of single‐crystalline molybdenum trioxide (α‐MoO3 ) nanotubes (MONTs) on CNT surfaces is reported to build a 1D van der Waals (vdW) heterostructure. The chirality of the MONTs can be directly "seen" and their structural selectivity is revealed. First, the centralized distribution of the chiral angles of the MONTs indicates a preferential orientation due to the anisotropic bending rigidity of the 2D layers. Then, the interlayer mismatching rejects the radial stacking of α‐MoO3 to maintain the single‐walled nature. These results provide a spontaneous strategy for the efficient recognition and control of chirality, and open up a new avenue for CNT‐based functional 1D vdW heterostructures. Abstract : Single‐crystalline molybdenum trioxide nanotubes (MONTs) are fabricated on carbon nanotube (CNT) templates. Single‐crystalline and single‐walled MONTs are prepared by van der Waals epitaxy on CNT templates. The chiral angles of the MONTs can be directly observed under an electron microscope. The MONTs show a preferred orientation with the [001] direction along the CNT axis due to the anisotropic bending rigidity of the monolayers.